DAMPAK PEMODERASIAN KOMPONEN ARUS KAS TERHADAP HUBUNGAN LABA AKUNTANSI DENGAN RETURN SAHAM - Hermawan, Hendy (Jurnal Ekonomi Modernisasi, 2012)
Accurate information regarding listed companies is crucial to minimize investment risk. This research aims to examine the effect of accounting income on stock return, and the effect of cash flow from operation, cash flow from investment, and cash flow from financing activities respectively as moderating variables on the relationship between accounting income and stock return of manufacturer listed on the Jakarta Stock Exchange. There were 161 manufacturing companies listed during 2001 to 2005, and 39 of them are selected as sample research using purposive sampling method. With 5 year research period, there are 195 observations done. Data then are analyzed using multiple linear regressions. Results show that accounting income affect stock return significantly, which is shown by greater value of t count compare to t table. While cash flow from operation, investment, and financing activities are not able to moderate relationship between accounting income and stock return